Aerobic capacity in swimming, cycling and arm cranking in swimmers aged 11-13 years - Viktorija Maconyte; Loreta Stasiule; Antanas Juodsnukis; Ilona Judita Zuoziene; Arvydas Stasiulis (BMC, 2024)
Abstract Background This study aimed to compare the aerobic capacity in swimming, cycling and arm cranking in swimmers aged 11-13 years. Methods Eleven swimmers (mean age, 12.1 ± 1.0 years) performed three incremental exercise tests. One of the tests was performed under specific conditions (front crawl swimming), and the other two were under non-specific conditions (cycling and arm cranking). Data on the pulmonary gas exchange were recorded using the portable analyser MetaMax 3B (Cortex, Leipzig, Germany). One-way analysis of variance for repeated measures was employed to test the null hypothesis and determine statistically significant differences between the indicators obtained under specific and non-specific testing conditions. Pearson's correlation coefficient was calculated to assess the relationships between the indicators of the pulmonary gas exchange. Results The relative peak oxygen uptake (V̇O2peak) value during swimming was 49.3 ± 6.2 mL/kg/min, which was higher than that during arm cranking (39.6 ± 7.3 mL/kg/min; P < 0.01) but lower than that during cycling (54.3 ± 7.8 mL/kg/min; P < 0.01). The peak minute ventilation (V̇Epeak) value during swimming (84.9 ± 12.6 L/min) was higher than that during arm cranking (69.4 ± 18.2 L/min; P < 0.01) but lower than that during cycling (98.4 ± 15.4 L/min; P < 0.01). Strong positive correlations were observed in the absolute and relative V̇O2peak values between swimming and cycling (r = 0.857, P < 0.01; r = 0.657, P < 0.05) and between swimming and arm cranking (r = 0.899, P < 0.01; r = 0.863, P < 0.05). A strong positive correlation was also observed in V̇Epeak values between swimming and arm cranking (r = 0.626, P < 0.05). Conclusion Swimmers aged 11-13 years showed V̇O2peak and V̇Epeak values during the specific swimming test greater than those during arm cranking but lower than those during cycling. However, aerobic capacity parameters measured during specific swimming conditions correlated with those measured during non-specific arm cranking and cycling conditions.